Economies of scale in Kansas beef cow-calf production - Stryker, L.; Langemeier, Michael R.; Jones, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Cow-calf producers must learn to control those aspects of production that are under their management. Quantity of beef produced and the cost of maintaining the breeding herd from conception to weaning are two examples of variables over which an individual operator has control. Therefore, it is important for managers to know their cost of production and, in turn, the relationship of quantity produced to cost. Our study found that for a 1% increase in quantity of beef produced, total cost increased by only 0.88%, suggesting economies of scale.
Keywords: Beef; Cow-Calf; Total cost; Economies of scale